HUBUNGAN ADIKSI SMARTPHONE DENGAN KESEHATAN MENTAL MAHASISWA - Ayu Deka Wati (Masker Medika, 2024)
Background: Various changes in people's lives due to the increasing progress of science and technology give rise to various problems for those who are unable to adapt. Early semester students who are still teenagers need to receive serious attention because during this period there is rapid physical and psychological growth. Adolescents' brains develop in a constant state so they tend to carry out risky behavior and pay less attention to the consequences of their actions compared to adults, including their ability to regulate smartphone use so that addictive behavior may arise. Objective: to find out the relationship between smartphone addiction and students' mental health. Research Method: Sampling was carried out using probability sampling and simple random sampling techniques, the number of respondents was 97 people. The instruments used were the Smartphone Addiction Scale Short Version (SAS-SV) questionnaire for adolescents and the Mental Health Continuum-Short Form (MHC-SV) questionnaire. Results: The data analysis process was carried out using the Mann Whitney alternative test and the Asymp value was obtained. Sig (2-tailed) is 0.039 (0.039 < 0.05) Conclusion: it can be concluded that Ho is accepted and Ha is rejected, which means there is a relationship between smartphone addiction and students' mental health.